2018
DOI: 10.1021/acs.jmedchem.8b00139
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and Evaluation of the First Fluorescent Antagonists of the Human P2Y2 Receptor Based on AR-C118925

Abstract: The human P2Y2 receptor (hP2Y2R) is a G-protein-coupled receptor that shows promise as a therapeutic target for many important conditions, including for antimetastatic cancer and more recently for idiopathic pulmonary fibrosis. As such, there is a need for new hP2Y2R antagonists and molecular probes to study this receptor. Herein, we report the development of a new series of non-nucleotide hP2Y2R antagonists, based on the known, non-nucleotide hP2Y2R antagonist AR-C118925 (1), leading to the discovery of a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 27 publications
1
46
0
Order By: Relevance
“…Furthermore, the management of radioactive waste is becoming increasingly regulated and expensive. To circumvent these issues, techniques using fluorescently labeled ligands like flow cytometry and the recently described BRET-based binding assay 10,11 , which has been adapted to several G-protein coupled receptors (GPCRs) [12][13][14][15][16][17][18][19][20][21][22][23][24] , have gained great importance.…”
mentioning
confidence: 99%
“…Furthermore, the management of radioactive waste is becoming increasingly regulated and expensive. To circumvent these issues, techniques using fluorescently labeled ligands like flow cytometry and the recently described BRET-based binding assay 10,11 , which has been adapted to several G-protein coupled receptors (GPCRs) [12][13][14][15][16][17][18][19][20][21][22][23][24] , have gained great importance.…”
mentioning
confidence: 99%
“…Furthermore, the assay is truly homogenous with no wash or lysis step necessary, enabling kinetic measurements of ligand binding to be performed with relative ease which would be time-consuming and cumbersome in traditional radio-ligand binding studies. Indeed, due to its relative ease of use and adaptability, since the initial description of NanoBRET ligand binding, this method has been used in a variety of binding modes (saturation, kinetic or competition) to investigate fluorescent ligand binding at a number of GPCRs including: adenosine A1 and A3, as well as angiotensin II receptor type 1 17 ; β1 and β2-adrenoceptors 17,19 ; free fatty acid receptors 1 and 2 20,21 ; histamine H1, H3 and H4 receptors 22,23 ; relaxin family peptide receptor 3 24 ; and P2Y2 receptor 25 . It has also been used to study the receptor tyrosine kinase vascular endothelial growth factor 2 26 and its co-receptor neuropilin-1 27 .…”
Section: Introductionmentioning
confidence: 99%
“…NanoBRET offers an attractive alternative to traditional radioligand binding, particularly given the safety issues regarding use of radioactive isotopes. Since it was first described by Stoddart et al (2015), the NanoBRET ligand binding assay has been used in numerous studies (Christiansen et al, 2016; Soave et al, 2016; Hansen et al, 2017; Kilpatrick et al, 2017; Wang et al, 2017; Alcobia et al, 2018; Conroy et al, 2018; Mocking et al, 2018; Peach et al, 2018; Stoddart et al, 2018; Hoare et al, 2019), including where the receptor is expressed under endogenous promotion (initiation of transcription by an endogenous promoter rather than one transfected in; White et al, 2019). Additionally, as ionizing radiation is not required for NanoBRET, this enables the characterization of low affinity ligands with micromolar concentrations.…”
Section: Nanoluciferase (Nanoluc; Nluc) and Nanobretmentioning
confidence: 99%
“…In order to monitor ligand binding with NanoBRET, appropriate fluorescent ligands are required to act as energy acceptors. Multiple studies have now demonstrated successful construction, validation, and use of fluorescent ligands to conduct NanoBRET ligand binding studies (Stoddart et al, 2015, 2018; Christiansen et al, 2016; Soave et al, 2016; Hansen et al, 2017; Kilpatrick et al, 2017; Wang et al, 2017; Alcobia et al, 2018; Conroy et al, 2018; Peach et al, 2018; Hoare et al, 2019). Three fluorescent dyes that have been used as conjugates to ligands for BRET studies are TAMRA, BODIPY, and 4-nitro-7-aminobenzofurazan (NBD).…”
Section: Novel Fluorescent Bret Acceptorsmentioning
confidence: 99%